Management of diabetic ketoacidosis: Role of Rapid Acting Insulin Analogs in comparison to regular intravenous insulin. - Ahmed , Ibrar; Sabir Ali, Sobia; Ali, Zafar; Mohammad Nawaz; Ghaffar, Tahir (International Journal of Endorsing Health Science Research, 2021)
Background: Diabetic ketoacidosis (DKA) is an acute metabolic healthcare crisis in patients with diabetes mellitus. The current study aimed to compare the effectiveness of rapid-acting insulin analog administered subcutaneously with regular insulin infused intravenously among the DKA patients. Methodology: In this prospective open labelled study, 100 consecutive DKA patients were randomly assigned to two groups. Group 1 patients were admitted to the intensive care unit (ICU) and treated with intravenous regular insulin infusion. Group 2 patients were managed in the emergency medical ward with subcutaneous rapid-acting insulin. Response to the therapy was assessed by the follow-up investigations of the biochemical parameters, including blood glucose concentration, serum ketones, pH, serum electrolytes including bicarbonates, sodium and potassium concentration until the resolution of DKA. Furthermore, the overall duration of therapy (blood glucose level < 250 mg/dl), time and amount of insulin administered until the resolution of DKA, were also assessed. Results: The baseline clinical and biochemical parameters were similar between the two treatment groups except for blood glucose and sodium concentration. The mean random blood sugar (RBS), acid-base parameters and concentration of ketone bodies were significantly improved from admission until the resolution of DKA. There was no significant difference in the duration of therapy (p=0.07). While the time and amount of insulin therapy required until resolution of DKA were significantly reduced among the patients treated subcutaneously with rapid-acting insulin, i.e. 16.36 ± 6.92 hrs and 59.28 ± 30.05 units (p<0.05). Conclusion: The patients with less complicated DKA can be managed with rapid-acting insulin analog in the medical wards obviating the need for admission to the ICU. With relatively better outcomes, it is an effective alternative to regular intravenous insulin infusion for DKA resolution.